Characteristic fast H− ion conduction in oxygen-substituted lanthanum hydride - Keiga Fukui (Nature Portfolio, 2019)
Hydride ions are promising for energy storage since they are abundant, lightweight, and highly mobile, but ionic conductivity should be improved. Here the authors achieve fast hydride ion conductivity in a mixed-anion compound by tuning oxygen content.